A composite material of zinc surface modified double hydroxide and its preparation method and application

By modifying the double hydroxide composite material on the zinc surface and the high-entropy reversible reaction, the energy efficiency of the electrochemical energy storage device is improved, the power waste caused by battery internal resistance and polarization is solved, and the thermal power of high-temperature charging and low-temperature discharge is realized Conversion significantly increases the P and EE values ​​of the battery.

CN117374243BActive Publication Date: 2024-12-24CENT SOUTH UNIV +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202311305354.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-10-09
Publication Date
2024-12-24
Estimated Expiration
2043-10-09

AI Technical Summary

Technical Problem

The energy efficiency (EE) of existing electrochemical energy storage devices is low, mainly due to the waste of electricity caused by internal resistance and polarization of the battery. Especially in aqueous zinc ion batteries, both P value and EE are less than 90%, limiting their application.

Method used

Using zinc surface modified double hydroxide composite material as electrode, the ZnaMx(SO4)y(OH)z·wH2O structure is formed by introducing high-entropy reversible reactions on the zinc surface, thereby increasing the temperature coefficient α of the electrochemical energy storage device, thereby improving the P value and EE value, and through high-temperature charging and low-temperature discharge methods, waste heat is converted into electrical energy, saving charging electrical energy.

Benefits of technology

The P value and EE value of the electrochemical energy storage device are effectively improved, making it exceed 100%, and at the same time, the charging power of the electrochemical energy storage device is greatly saved and the energy efficiency is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117374243B_ABST
    Figure CN117374243B_ABST
Patent Text Reader

Abstract

The present invention provides a composite material of zinc surface modified double hydroxide and a preparation method and application thereof. The composite material comprises a base layer and a modification layer. The base layer comprises zinc metal and / or zinc alloy. The structural formula of the modification layer is: Zn a M x (SO4) y (OH) z ·wH2O; M is at least one of Fe, Mn, Cu, Co, Mg and Ni; the present invention introduces a high entropy reversible reaction by modifying a double hydroxide material with a hydrotalcite-like structure on the surface of zinc. The composite material is used as an electrode to enable an electrochemical energy storage device to have a larger temperature coefficient α, thereby improving the P value and EE of the electrochemical energy storage device and improving the cycle stability of the electrochemical energy storage device; the present invention also provides a method for improving the energy efficiency of the electrochemical energy storage device, which effectively saves the charging energy of the electrochemical energy storage device by charging the battery at high temperature and discharging the battery at low temperature, thereby improving the energy efficiency of the electrochemical energy storage device.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of battery materials, and more specifically, to a zinc surface modified layered double hydroxide composite material, a preparation method and application thereof, and a method for improving the energy efficiency of an electrochemical energy storage device. Background Art

[0002] Electrochemical batteries, with their fast response speed, high specific energy, and good cycle stability, have effectively realized the peak load shifting of the power grid and alleviated the peak power supply pressure, and have been widely used in energy storage power stations. However, the energy efficiency (EE) of batteries is still a problem, which greatly limits their application in large-scale energy storage. EE is the ratio of discharge energy to charge energy, which is equal to P×CE, where P is the ratio of average discharge voltage to average charge voltage. CE is the Coulombic efficiency. Figure 1 As shown in (a), under normal circumstances, the CE of most batteries is basically above 99%, but the P value is less than 95%, resulting in poor EE. This is mainly due to the existence of battery internal resistance and polarization, which makes the battery charging voltage higher than the reaction potential and lower than the reaction potential during discharge. Specifically, the average discharge voltage of the battery is lower than the average charging voltage, which is bound to cause a waste of electrical energy. Especially in aqueous zinc-ion batteries, the P value and EE are both less than 90% ( Figure 1 (a)). In recent years, there have been a lot of studies on improving EE values ​​in zinc ion aqueous solution batteries, such as: β-MnO2@SWCNT / Zn (82.21%, Advanced Materials, 2022, 34(18): e2109872), NH4V4O 10 / Zn(68.84%, Advanced Materials, 2022, 34(37):e2200677), Zn 0.25 V2O5·nH2O / Zn(86.32%,Nature Energy,2016,1(10):16119), Cu3(HHTP)2 / Zn(81.56%,Nature Communications,2019,10(1):4948), MnVO / Zn(70%,Energy&Environmental Science,2019,12(7):2273-2285), MnO2 / Zn(82.69%,Energy&Environmental Science,2023,16(5):2133-2141). However, aqueous zinc-ion batteries still have large power loss, which limits their use. Therefore, it is necessary to further improve the P value and EE. Summary of the invention

[0003] Based on the above technical problems existing in the prior art, one of the objects of the present invention is to provide a composite material of zinc surface modified double hydroxide, by modifying a double hydroxide material with a hydrotalcite-like structure on the zinc surface and introducing a high entropy reversible reaction. The composite material is used as an electrode in an electrochemical energy storage device, so that the electrochemical energy storage device can have a larger temperature coefficient α, thereby improving the P value and EE of the electrochemical energy storage device, and at the same time improving the cycle stability of the electrochemical energy storage device.

[0004] In order to achieve the above object, the technical solution of the present invention is as follows:

[0005] A composite material of zinc surface modified double hydroxide (Layered Double Hydroxides, LDH), the composite material comprises a base layer and a modification layer, the base layer comprises zinc metal and / or zinc alloy, the structural formula of the modification layer is: Zn a M x (SO4) y (OH) z wH2O(Zn-LDH); wherein a=1-5, x=0.5-3, y=0.3-3, z=3-10, w=1-5, M is Fe 2+ , at least one of Mn, Cu, Co, Mg and Ni.

[0006] In some embodiments, the modification layer is composed of Zn(OH)2 and M(OH)2, and the interlayer is composed of ZnSO4, -OH and H2O.

[0007] In some embodiments, the structural formula of the modified layer is: Zn a Ni x (SO4) y (OH) z ·wH2O.

[0008] In some embodiments, the substrate layer is pure zinc metal, zinc alloy, or other metals or alloys having a zinc metal surface layer or a zinc alloy surface layer.

[0009] A second object of the present invention is to provide a method for preparing the composite material of any of the above embodiments, the method comprising the following steps:

[0010] Removing the oxide layer on the surface of the substrate layer, using the substrate layer as a negative electrode, assembling a battery with a positive electrode and an electrolyte, and performing constant current charge / discharge (GCD) at a current density of 0.01-50 mA / g for at least one cycle to obtain the composite electrode material;

[0011] The active material of the positive electrode is M'HCF, and the electrolyte includes Zn 2+ 、M 2+ 、SO4 2- ions, wherein M' in the positive electrode active material includes Ni 2+ , Cu 2+ , Mn 2+ , Fe 2+ At least one of .

[0012] In some embodiments, in the electrolyte, Zn 2+ The concentration is 0~4M, M 2+ The concentration is 0~3M, SO4 2- The concentration is 0~3M.

[0013] In some embodiments, the preparation method specifically comprises the following steps:

[0014] The substrate layer is immersed in an acid solution to remove the surface oxide layer, making the surface of the substrate layer porous; then the substrate layer is rinsed with deionized water and polished to silvery white. 2+ 、Ni 2+ and SO4 2- The composite material is obtained by performing constant current charge and discharge in an electrolyte at a current density of 0.01-50 mA / g for at least one cycle.

[0015] In some embodiments, the concentration of the acid solution is 0.5-5 vol%.

[0016] In some embodiments, the acid solution is dilute hydrochloric acid.

[0017] A third object of the present invention is to provide an application of the composite material of any of the above embodiments as an electrode material.

[0018] A fourth object of the present invention is to provide an electrochemical energy storage device, the electrochemical energy storage device comprising a negative electrode, the negative electrode comprising the composite material described in any one of the above embodiments.

[0019] In some embodiments, the electrochemical energy storage device further comprises a positive electrode, wherein the positive electrode comprises an active material, wherein the active material is M'HCF, and wherein M' comprises Ni 2+ , Cu 2+ , Mn 2+ , Fe 2+ At least one of .

[0020] In some embodiments, the positive electrode further includes a conductive agent and a binder, and the mass ratio of the active material, the conductive agent and the binder is 70-80:10-20:10-20.

[0021] In some embodiments, the electrochemical energy storage device further comprises an electrolyte comprising KCF3SO3, Zn(CF3SO3)2 and NiSO4.

[0022] In some embodiments, in the electrolyte, the concentration of KCF3SO3 is 0 to 3 M, the concentration of Zn(CF3SO3)2 is 0 to 4 M, and the concentration of NiSO4 is 0 to 3 M. The concentrations of KCF3SO3, Zn(CF3SO3)2, and NiSO4 are all greater than 0.

[0023] A fifth object of the present invention is to provide a method for improving the energy efficiency of an electrochemical energy storage device, the method comprising: charging the electrochemical energy storage device at 40 to 100° C. and discharging the electrochemical energy storage device at 0 to 25° C.; the electrochemical energy storage device is the electrochemical energy storage device described in any of the above embodiments.

[0024] In some embodiments, the electrochemical energy storage device is charged at 50°C and discharged at 5°C.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] The present invention modifies the surface of the zinc-containing matrix layer with a double hydroxide material having a hydrotalcite-like structure having a specific structure, so that the composite material has good stability. In addition, a high entropy reversible reaction is simultaneously introduced into the double hydroxide, and the composite material is used as an electrode material in an electrochemical energy storage device, so that the electrochemical energy storage device has a large temperature coefficient α, thereby effectively improving the P value and EE value of the electrochemical energy storage device, so that the P value and EE value are respectively more than 100%.

[0027] In addition, the present invention also provides a method for improving the energy efficiency of an electrochemical energy storage device, by performing high-temperature charging and low-temperature discharging on a battery, thereby converting waste heat into electrical energy, greatly saving the charging energy of the electrochemical energy storage device, and improving the energy efficiency of the electrochemical energy storage device. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 In the figure, (a) shows the average discharge and charge voltage ratios and energy efficiency examples of four types of batteries; (b) shows a schematic diagram of the electrochemical Stirling cycle and the charging energy saved in a cycle (α cell <0);

[0029] Figure 2 The scanning electron microscope image and energy spectrum of NiHCF;

[0030] Figure 3 is the XRD pattern of NiHCF powder;

[0031] Figure 4 The XPS full spectrum and fine spectrum of NiHCF powder;

[0032] Figure 5 Schematic diagram of the crystal structure of Zn-LDH;

[0033] Figure 6 The morphology and element distribution diagrams of Zn-LDH electrodes of different sizes, where (a) is the SEM image, and (b) and (c) are TEM images;

[0034] Figure 7 In the figure, (a) is the XRD pattern of the Zn-LDH electrode; (b) is the FTIR and Raman spectrum of the Zn-LDH electrode;

[0035] Figure 8 XPS measurement and fine scanning image of Zn-LDH electrode;

[0036] Fig. 9 The in-situ XRD pattern of the Zn-LDH electrode and its corresponding charge-discharge curve;

[0037] Fig.10 Energy spectrum, XRD spectrum, Fourier transform infrared spectrum, and Raman spectrum of Zn-LDH electrode at different capacities; (a), (b), (c), and (d) are energy spectrum, XRD spectrum, Fourier transform infrared spectrum, and Raman spectrum, respectively;

[0038] Fig.11 The SEM morphology, XRD spectrum, FTIR spectrum, and Raman spectrum of Zn-LDH electrodes with different cycle numbers; (a)-(c) are SEM morphology; (d) is an XRD spectrum; (e) is an FTIR spectrum; (f) is a Raman spectrum;

[0039] Fig.12 The NiHCF / Zn and NiHCF / Zn-LDH systems were tested at room temperature and a current density of 11.2 mA g -1 The cyclic voltammetry curve comparison diagram and the charge-discharge curve comparison diagram are shown below; wherein, (a) is a cyclic voltammetry curve comparison diagram; (b) is a charge-discharge curve comparison diagram;

[0040] Fig.13 Figure 1 shows the rate performance of NiHCF / Zn-LDH battery at different current densities (a); (b) shows the rate reversibility performance of NiHCF / Zn-LDH battery at different current densities (c); and (d) shows the rate reversibility performance of NiHCF / Zn and NiHCF / Zn-LDH batteries at a current density of 56 mA g -1 Cyclic stability test diagram under conditions;

[0041] Fig.14 (a) shows the K in NiHCF / Zn and NiHCF / Zn-LDH systems. + Concentration on + (b) The influence of Zn in NiHCF / Zn and NiHCF / Zn-LDH systems 2+ Concentration on - (c) is the response diagram of the positive and negative electrode potentials to temperature; (d) is the potential difference-temperature difference diagram of a single electrode and a full battery;

[0042] Fig.15 The schematic diagram of the charging reaction of NiHCF / Zn-LDH battery and the entropy increase mechanism diagram of the reversible reaction of LDH in the anode;

[0043] Fig.16 (a) shows the cyclic voltammetry curves of the NiHCF / Zn-LDH system at different temperatures, and (b) shows the cyclic voltammetry curves of the NiHCF / Zn-LDH system at a current density of 11.2 mA g -1 Comparison of charge and discharge curves under different conditions;

[0044] Fig.17 The Nysted plot of NiHCF / Zn-LDH system at different temperatures;

[0045] Fig.18 In four charge and discharge modes, 28mA·g -1 Constant current charge and discharge curves under current density;

[0046] Fig.19 (a) shows the charge and discharge curves of NiHCF / Zn-LDH battery at different temperature differences, where the current density is 11.2 mA g -1 , the solid line is the charging curve, and the dotted line is the discharging curve; (b) The figure shows the charging and discharging curves of the NiHCF / Zn-LDH battery at different current densities; (c) The figure shows the P value of the NiHCF / Zn-LDH battery at different temperature differences and current densities; (d) The figure shows the EE value of the NiHCF / Zn-LDH battery at different temperature differences and current densities, where the colored surface is fitted by the experimental data;

[0047] Fig. 20 is the value of η under different temperature differences and current densities, where the colored surface is fitted by the experimental data;

[0048] Fig.21 The energy saved in a complete electrochemical Stirling cycle (11.2 mA g -1 );

[0049] Fig. 22 The cycle performance of thermal charging, where the current density is 28 mA g-1 , the solid line is the charging curve, and the dotted line is the discharging curve;

[0050] Fig.23 The cycle performance of conventional charge and discharge, where the current density is 28 mA g -1 , the solid line is the charging curve, and the dotted line is the discharging curve;

[0051] Fig.24 The P value & EE-cycle number diagram of NiHCF / Zn-LDH battery at 50℃ charging, 5℃ discharging and 5℃ constant temperature charging and discharging;

[0052] Fig.25 Actual pictures of the charging voltage of NiHCF / Zn-LDH soft-pack battery at (a) 48°C and (b) 5°C. DETAILED DESCRIPTION

[0053] Many specific details are set forth in the following description to facilitate a full understanding of the present invention. However, the present invention can be implemented in many other ways than those described herein, and those skilled in the art can make similar modifications without violating the connotation of the present invention, so the present invention is not limited to the specific implementation disclosed below.

[0054] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.

[0055] In the following specific implementation manner, the characterization of the material is detected by the following instruments:

[0056] Scanning electron microscopy (SEM) and energy dispersive spectrometer (EDS) of the prepared NiHCF and Zn-LDH electrodes were collected on a JEOL / JSM-7610FPlus field emission scanning electron microscope (SEM);

[0057] XRD studies were performed on an Ultima IV X-ray diffractometer using Cu Kα radiation (40 kV, 40 mA, );

[0058] X-ray photoelectron spectroscopy (XPS, Thermo Scientific K-Alpha) was used to detect the surface element information. The Thermo Nicolet 6700 instrument collected its Fourier transform infrared spectrometer (FTIR) spectrum;

[0059] Raman characterization was performed using a Raman spectrometer (inVia Reflex) under excitation at 532 nm;

[0060] The research was carried out using a JEOL / JEM-F200 high-magnification transmission electron microscope (TEM).

[0061] The electrochemical measurement method is as follows:

[0062] In the present invention, all temperature coefficient measurements are performed in a sealed electrolytic cell using a three-electrode device, wherein NiHCF is used as a working electrode (WE), Zn or Zn-LDH is used as a counter electrode (CE), and Hg / Hg2Cl2 is used as a reference electrode (RE). The voltage and temperature changes of the battery are monitored by a voltage channel and a thermocouple channel, respectively. In addition, all cyclic voltammetry curves and charge-discharge curve measurements are performed in a sealed electrolytic cell using a three-electrode configuration, wherein NiHCF is used as a working electrode (WE), Zn or Zn-LDH is used as a counter electrode (CE) and a reference electrode (RE). 0.5M KCF3SO3 and 0.05MZn(CF3SO3)2 are used as mixed electrolytes for NiHCF / Zn batteries. On this basis, 0.05M NiSO4 is added as a mixed electrolyte for NiHCF / Zn-LDH batteries.

[0063] The present invention aims to solve the problem of small P value and EE value in electrochemical energy storage devices in the prior art, and proposes a method for charging a battery using waste heat and electrical energy at the same time ( Figure 1 (b)), which greatly improves the P value and EE of the battery. In the present invention, we use the electrochemical cycle of the battery to simulate the Stirling cycle and charge the battery at high temperature (T H ) and normal temperature discharge (T L ), which converts waste heat into electrical energy and saves battery charging energy. Compared with traditional waste heat power generation technology, this technology does not have heat conduction loss caused by temperature difference. In addition, when the battery works at a small current, the charging and discharging process is close to equilibrium, and has a large thermoelectric conversion efficiency (η, represented by formula (1)).

[0064]

[0065] In formula (1), W is the difference between the normal charging energy and the high temperature charging energy in one cycle. H It is T H The amount of heat absorbed when HR is the additional energy required to heat the battery. E loss It is the energy loss caused by the internal resistance of the battery. ΔS is the change in entropy of the electrochemical reaction in one cycle. ΔT=T H -T L , C P is the heat capacity of the entire battery. HR is the heat recovery rate, which indicates the proportion of energy released during cooling that can be reused in the heating process.

[0066] In this cycle, the voltage of hot charging is much lower than that of normal charging, so that the P value and EE of the battery are both higher than 100%. Among them, the key parameter P can be expressed as equation (2):

[0067]

[0068] In formula (2), is the average voltage. The subscripts “dis” and “ch” represent discharge and charge, respectively. is the charging voltage at different temperatures. α is the absolute value of the temperature coefficient (α=ΔV / ΔT=ΔS / nF), which is the determining factor for thermal charging. cell <0 as an example, Figure 1 As shown in (b), by charging the battery at a lower voltage at a high temperature and then discharging it at a higher voltage at a normal temperature, both the P value and the EE can be higher than 100%. Figure 1 The area enclosed by the closed loop ACDB in (b) is the energy saved by thermal charging compared to conventional charging. cell The larger the value, the more charging energy is saved. The area enclosed by the closed loop CDEF is the total amount of electrical energy converted from heat energy in the electrochemical Stirling cycle. Therefore, in order to save more charging energy, a larger α is required to obtain a higher P value and EE.

[0069] Based on this, the present invention provides a composite material of zinc surface modified double hydroxide, the composite material comprises a base layer and a modification layer, the base layer comprises zinc metal and / or zinc alloy, the structural formula of the modification layer is: Zn a M x (SO4) y (OH) z ·wH2O; wherein a=1-5, x=0.5-3, y=0.3-3, z=3-10, w=1-5, and M is at least one of Fe, Mn, Cu, Co, Mg and Ni.

[0070] In the present invention, we have Zn / Zn 2+ If a high entropy reversible reaction is introduced into the electrode, the reaction will proceed in the direction of increasing entropy at high temperature and decreasing entropy at low temperature. The addition of reversible reaction greatly increases the effect of temperature on the electrode reaction, resulting in large changes in ΔS and α. 2+ A high entropy reversible reaction as shown in equation (3) is introduced into the electrode, and the equilibrium constant of the reversible reaction is recorded as K. Then there are two competing reactions (4) and (5) in the zinc anode, with proportions of l and (1-l) respectively, and the corresponding temperature coefficients are recorded as α1 and α2 respectively, so the total temperature coefficient of the zinc anode is α min =α1*l+α2*(1-l).

[0071]

[0072]

[0073]

[0074]

[0075]

[0076] Where J is the correction factor for ion concentration. and are the standard temperature coefficients of reaction equations (4) and (5) respectively. n are the reactants of high entropy reversible reaction, B1, B2, ···, B n It is the product of high entropy reversible reaction. Zn 2+ 、A1、A2、···、A n The concentrations are denoted as x, A1, A1, ··, A n When there is Δx mol of Zn at the anode, it loses electrons to form Zn 2+ When the equilibrium reaction (3) shifts to the right, Zn 2+ Reduce m mol and eventually reach a new equilibrium. So,

[0077]

[0078]

[0079]

[0080]

[0081]

[0082] definition So there is

[0083]

[0084] Among them, U, M and H are parameters related to ion concentration and stoichiometric coefficient in reversible reactions. By α mix The derivation results show that when the zinc ion concentration is high, the anode reaction is mainly reaction (4), α mix Reduce to When the zinc ion concentration is low, the anode is dominated by reaction (5), α mix Increase to α2e -U-Mln(C Zn 2+ ).

[0085] Specifically, the modification layer is composed of Zn(OH)2 and M(OH)2, and the interlayer is composed of ZnSO4, -OH and H2O.

[0086] Furthermore, we calculated Fe 2+ , Mn 2+ , Cu 2+ ,Co 2+ ,Mg 2+ and Ni 2+ The reaction energy of six ions participating in the reversible reaction. 2+ As an example, when Ni 2+ When participating in the reaction, stable ZnNi with hydrogen bonds between layers can be generated x (SO4) y (OH) z wH2O(Zn-LDH) hydrotalcite structure, the reaction formula is as follows:

[0087]

[0088] Specifically, the specific implementation of the solution of the present invention is as follows:

[0089] 1. Preparation and characterization of NiHCF

[0090] In this paper, NiHCF was synthesized by co-precipitation method at room temperature, and all reagents used were of analytical purity.

[0091] First, under strong magnetic stirring, 100 mL of 30 mM Ni(NO3)2 was dripped into 100 mL of 15 mM K3Fe(CN)6 at a rate of one drop per second, and the solution turned yellow. After the solution was completely mixed, it was matured for 30 minutes under magnetic stirring, and then the mixed solution was ultrasonically treated for 30 minutes. The precipitate was then centrifuged and washed three times with deionized water. Finally, the product was vacuum dried at 40°C for 12 hours to obtain the target sample (i.e., NiHCF).

[0092] In addition to being prepared by the above method of the present invention, NiHCF can also be prepared by any method disclosed in the prior art or purchased commercially.

[0093] The prepared NiHCF was characterized and the results were as follows: Figure 2-4As shown. The SEM and EDS images of the sample are shown in Figure (2). Obviously, the material has a nearly circular flake structure with a particle size of less than 100nm. The energy spectrum verifies the atomic percentage and shows that the elements in the material are evenly distributed. The XRD spectrum shows (Figure (3)) that the diffraction peaks of the prepared material match the standard card PDF#51-1897, proving that KNiFe(CN)6(NiHCF) was successfully prepared in this paper. As shown in Figure (4), according to the XPS full spectrum and fine scanning results of NiHCF powder, it can be seen that nickel is Ni 2+ Iron exists in the form of Fe 3+ This is consistent with the XRD characterization results.

[0094] 2. Preparation of NiHCF Electrode

[0095] 70 wt% NiHCF powder, 20 wt% acetylene black and 10 wt% polyvinylidene fluoride (PVDF) were mixed with N-methyl-2-pyridone (NMP) and stirred for several hours to prepare NiHCF electrode slurry. The obtained slurry was applied on an area of ​​1×2 cm 2 The samples were placed on a titanium mesh and dried in a vacuum oven at 70 °C. The mass loading of active material was about 5 mg cm -2 .

[0096] 3. Preparation of Zn-LDH Electrode

[0097] The preparation of Zn-LDH includes the following steps:

[0098] (1) immersing the zinc sheet in 3 vol% dilute hydrochloric acid to remove the surface oxide layer and make the surface of the zinc sheet corroded and porous; after rinsing with deionized water, the zinc sheet is polished to a silvery white color;

[0099] (2) An aqueous K / Zn mixed ion battery was constructed using the zinc sheet treated in step (1) as the negative electrode, the above-mentioned NiHCF electrode as the positive electrode, and a mixed solution consisting of 0.5 M KCF3SO3, 0.05 M Zn(CF3SO3)2 and 0.05 M NiSO4 as the electrolyte. The battery was then charged at 0.1 mA g -1 The constant current charge and discharge cycle was carried out with a current of , and the negative electrode was disassembled to obtain the Zn-LDH electrode.

[0100] The obtained Zn-LDH electrode was characterized and the results were as follows Figure 5-8 shown.

[0101] like Figure 5 As shown, the Zn-LDH electrode obtained by the present invention is composed of Zn(OH)2 and Ni(OH)2 on the upper layer, and ZnSO4, hydroxyl and water between the layers. Due to the formation of hydrogen bonds between the layers, the multilayer structure of Zn / Ni-LDH has good stability.

[0102] like Figure 6 As shown in the figure, the morphology is a two-dimensional sheet structure of several microns in size, which is consistent with the characteristic structure of bimetallic layered double hydroxides (LDHs). The energy spectrum results in SEM and TEM show that Zn, Ni, S, and O elements are evenly distributed at different sizes, and the molar ratio of Ni:S is close to 1:1. Interestingly, the XRD spectrum of the new phase ( Figure 7 (a)) is different from common Zn metal, ZnO, Zn(OH)2 and Zn4(OH)6SO4·0.5H2O compounds, but is different from Zn 3.52 Ni 1.63 (SO4) 1.33 (OH) 7.64 The interlayer characteristic peaks (110) and (120) of 4.67H2O are in good agreement, indicating that a new phase with LDH structure is formed on the zinc electrode.

[0103] Figure 7 The FTIR and Raman spectra of (b) show that most of the characteristic peaks can correspond to the characteristic bands of LDH compounds. -1 The characteristic peaks are due to the vibration of metal-oxygen (Zn / Ni-O) and metal-hydroxyl (Zn / Ni-OH) groups in LDHs crystals. -1 and 1122cm -1 The vibration at is attributed to SO4 2- This is consistent with the vibration peak of the interlayer sulfate anion in Zn-LDH. -1 The H2O bending vibrations that can be attributed to interlayer water indicate that there is a strong interaction between interlayer water and other elements. Figure 8 The full XPS spectrum and fine scanning spectrum of the Zn-LDH electrode show that the Zn-LDH electrode contains Zn, Ni, S and O elements, and the Zn 2p 3 / 2 The peak value of Ni 2p is at 1021.76 eV, which is close to that of Zn(OH)2. 3 / 2 The peak value is located at 855.78 eV, indicating that nickel is Ni 2+ The peak position of O1s is 531.48eV, indicating that oxygen exists in the form of metal MO bond; S2p 3 / 2 The peak position of the Zn / Ni layered double hydroxide was 168.46 eV, indicating that the sulfur element was in the form of metal sulfate.

[0104] In order to study the reaction process of LDH compounds during charge and discharge, we performed in situ XRD, EDS, FTIR and Raman tests on the battery at different capacities. Fig. 9 This is an in-situ XRD pattern collected during a charge-discharge cycle in the voltage range of 1.9 to 1.1 V. At the beginning of discharge, a new diffraction peak appears at 32.8°, which belongs to the new phase of Zn-LDH, indicating that LDH is gradually generated during the discharge process. At the same time, we used ex-situ XRD to test the change of the characteristic peak intensity of Zn / Ni-LDH with the battery capacity ( Fig.10 (b)), the same result as in situ XRD was obtained.

[0105] Depend on Fig.10 (a) It can be seen that as the battery capacity increases, the mass percentage of Ni and S elements on the electrode surface gradually decreases, and the molar ratio of Ni:S is close to 1:1. As the battery capacity increases, the H2O and SO4 2- The characteristic peaks of M-OH gradually increase, indicating that Zn-LDH is generated during the discharge process and gradually decomposes during the charge process ( Fig.10 (c)-(d)). We speculated on the electrochemical process of Zn-LDH as follows: after the introduction of the high entropy reversible reaction (Equation (9)), there are two competing reactions in the zinc anode (Equations (4) and (10)):

[0106]

[0107]

[0108] During the discharge process, as Zn 2+ As the concentration increases, the reaction proceeds toward the formation of LDH. 2+ With the increase of concentration, Zn-LDH continued to dissociate. It is worth noting that in the NiHCF / Zn-LDH system, LDH with good reversibility and cyclic stability was generated on the surface of the zinc anode.

[0109] To illustrate the stability of the Zn-LDH electrode, Fig.11 As shown in (a)-(c), the SEM images of the Zn-LDH electrode show that after 3 cycles, a new phase with a two-dimensional sheet structure is formed on the zinc surface, and it remains unchanged after 13 and 20 cycles. The anode after 3, 13 and 20 cycles of constant current charge and discharge was characterized by XRD, FT-IR and Raman spectroscopy, as shown in Fig.11 (d)-(f). The images show that the position and intensity of the characteristic peaks of Zn-LDH do not change significantly with the increase in the number of charge and discharge cycles. Obviously, Zn-LDH exhibits good stability during charge and discharge.

[0110] Fig.12 (a) and (b) are the cyclic voltammetry curves and constant temperature charge-discharge curves of NiHCF / Zn and NiHCF / Zn-LDH systems at room temperature, respectively. Fig.12 It can be seen that the redox peaks of the two systems are slightly different. Due to the thermodynamic advantage of introducing a reversible reaction in the Zn-LDH electrode, the NiHCF / Zn-LDH system has a smaller battery polarization. Afterwards, we performed GCD measurements of the NiHCF / Zn-LDH battery at different rates. The results are as follows: Fig.13 shown. Fig.13 (a) is the charge and discharge curve of NiHCF / Zn-LDH system at different rates, which clearly shows that the battery of this system has good high rate performance. Fig.13 (b) shows that when the current density is 0.1, 0.2, 0.5, 1, 2 and 3C, the capacity of the battery is 59.69, 58.84, 58.00, 57.12, 57.30 and 55.24 mAh g -1 When the current is restored to 0.1C, the reversible capacity can be recovered to 96.63% at 0.1C, confirming the high reversibility of the improved K / Zn ion hybrid battery. In addition, the cycling stability of NiHCF / Zn and NiHCF / Zn-LDH batteries was further evaluated, and the results are shown in Fig.13 The results show that the reversible capacity of the NiHCF / Zn-LDH battery is 58.86 mAh g after 500 GCD cycles at 1C. -1 , the capacity decay is less than 3%, indicating that the NiHCF / Zn-LDH battery has good cycle stability. However, the capacity of the NiHCF / Zn battery drops to 13.89% after 20 cycles. It can be seen from the experiment that due to the introduction of reversible reaction in the anode, the high rate performance and good reversibility of the modified battery have been greatly improved.

[0111] 4. Temperature coefficients of NiHCF / Zn and NiHCF / Zn-LDH systems

[0112] 1. In a three-electrode electrolytic cell with NiHCF (50% SOC) as the working electrode, Zn or Zn-LDH as the counter electrode, and saturated calomel electrode as the reference electrode, the effect of different ion concentrations on the temperature coefficient α of a single electrode is shown in the following table. Fig.14 As shown in Figures (a) and (b).

[0113] Depend on Fig.14 As shown in Figures (a) and (b), in the NiHCF / Zn system, the positive electrode temperature coefficient α + As the potassium ion concentration increases, the negative electrode temperature coefficient α- As the zinc ion concentration increases, it conforms to the Nernst equation. + It increases with the increase of potassium ion concentration, and α- also decreases with the increase of zinc ion concentration. This shows that the introduction of high entropy reversible reaction in NiHCF / Zn-LDH system increases the ion species and ion entropy change of the anode during the charge and discharge process, resulting in a significant deviation from the Nernst equation and obtaining a higher α- when the zinc ion concentration is low.

[0114] 2. In a three-electrode electrolytic cell, NiHCF (50% SOC) was used as the working electrode, Zn or Zn-LDH was used as the counter electrode, and a saturated calomel electrode was used as the reference electrode. When the temperature was gradually increased from 5°C to 50°C, the open circuit voltage changes of the positive and negative electrodes were recorded. The results are as follows: Fig.14 As shown in Figures (c) and (d), Figure (c) is the measured voltage-temperature curve, and (d) is the fitted potential difference-temperature difference curve. The results shown in Figure (c) show that in the NiHCF / Zn-LDH system, the positive and negative electrode voltages have a good response relationship to temperature. Figure (d) shows the relationship between the positive electrode (NiHCF), negative electrode (Zn or Zn-LDH) and full battery voltage with temperature difference in the NiHCF / Zn and NiHCF / Zn-LDH systems when the temperature is increased from 5°C to 50°C at a rate of 1°C / min. As can be seen from Figure (d), the slope of the positive and negative electrode potential difference with temperature difference is linear, and its value corresponds to the temperature coefficient α. The positive electrode potential decreases with increasing temperature, while the negative electrode potential increases with increasing temperature. In the NiHCF / Zn system, the positive electrode temperature coefficient is -0.554mV / K, the Zn negative electrode temperature coefficient is 0.667mV / K, and the full battery temperature coefficient is -1.221mV / K; in the NiHCF / Zn-LDH system, the positive electrode temperature coefficient is -0.827mV / K. Compared with the NiHCF / Zn system, the temperature coefficient of the positive electrode does not change much; while the temperature coefficient of the Zn-LDH negative electrode is 2.116mV / K, which is 3.17 times that of the negative electrode in the NiHCF / Zn system. Therefore, the full battery has a more negative temperature coefficient (-2.944mV / K), which is 2.41 times that of the full battery in the NiHCF / Zn system.

[0115] Schematic diagram of the charging reaction of NiHCF / Zn-LDH battery and the entropy increase mechanism of the reversible reaction of LDH in the anode are shown in the figure. Fig.15 As shown, the introduction of the reversible reaction of LDH greatly increases the entropy change of the anode reaction, thereby obtaining larger ΔS and α when the zinc ion concentration is low.

[0116] Fig.16(a) and (b) are the comparison diagrams of the cyclic voltammetry curves and constant temperature charge-discharge curves of the NiHCF / Zn-LDH system at 10℃, 30℃, and 50℃, respectively. Fig.16 It can be seen that the redox potential of the system decreases with increasing temperature, indicating that the NiHCF / Zn-LDH battery has a lower reaction potential at high temperature.

[0117] Fig.17 It is the Nester plot of NiHCF / Zn-LDH system at different temperatures, which shows that as the battery temperature increases, the internal resistance of the battery decreases and the ion mobility gradually increases.

[0118] 5. Study on thermal charging performance of NiHCF / Zn-LDH battery

[0119] From the above research results, it can be seen that the temperature coefficient of the NiHCF / Zn-LDH system full battery can reach -2.944mV / K, which means that the voltage of the full battery will increase as the temperature decreases. It can be actually applied to high-temperature charging and low-temperature discharging to achieve the dual purpose of saving charging energy and recovering waste heat.

[0120] This application also compares the charge and discharge curves of the battery at a 0.5C rate under four charge and discharge modes, such as Fig.18 As shown in Figures (a)-(d), the battery was charged and discharged at 50℃, charged and discharged at 5℃, charged and discharged at 5℃-50℃, and charged and discharged at 50℃-5℃. The experimental results show that the P values ​​of the battery are 98.86%, 88.69%, 85.61% and 103.35% under the four charge and discharge modes. The P value of the NiHCF / Zn-LDH battery applied to 50℃ charge-5℃ discharge is the highest, which is consistent with the theory.

[0121] 6. Effect of charge-discharge temperature difference and current density of NiHCF / Zn-LDH battery on thermal charging performance

[0122] Furthermore, we explored the effects of temperature difference and current density on the thermal charging performance of NiHCF / Zn-LDH batteries. Figure 19-21 shown.

[0123] At 11.2 mA g -1 The thermal charging performance of the battery at different temperatures and discharged at 5°C at a current density of 0.2C. Fig.19 (a) It can be seen that the average charging voltage decreases significantly with the increase of charging temperature. Moreover, when charging at different temperatures, the average discharge voltage difference at 5°C is less than 22mV. The fluctuation is mainly due to factors such as battery polarization.

[0124] In addition to the temperature difference, the battery's charging current density will also affect the battery's average charge and discharge voltage. We applied the battery to charge at 50°C and discharge at 5°C to explore the battery's thermal charging performance at different current densities. Fig.19 (b) It can be seen that the smaller the charging rate, the more charging energy is saved. This is mainly because the smaller the charging rate, the smaller the Joule heat of battery polarization and battery internal resistance, and the closer the entire cycle process is to a balanced state, resulting in a higher thermoelectric conversion efficiency. Fig.19 (c) and (d) and Fig. 20 The P value, EE value and thermoelectric efficiency η value under different temperature differences and current densities are shown respectively. The colored surface fitted by the experimental data further shows that the battery has a larger P value, EE value and η value at a lower current density and a larger temperature difference.

[0125] like Fig.21 As shown, at a current density of 11.2 mA g -1 The battery showed good thermal charging performance in a complete electrochemical Stirling cycle. In this cycle, a total of 7.97mWh·g -1 The battery thermoelectric efficiency reached 4.07% (29.24% of Carnot efficiency), which saved 13.26% of energy compared with normal charge and discharge. Finally, the experiment obtained a higher P value and EE value of 104.13% and 104.11% respectively.

[0126] The cycling performance of NiHCF / Zn-LDH battery at 50℃ charging and 5℃ discharging is shown in the following figure. Fig. 22 The cycle performance of constant temperature charge and discharge at 5°C is shown in Fig. 22 Experiments show that at high current density (28 mA g -1 ), NiHCF / Zn-LDH battery has good cycle performance and stability. In addition, we studied the changes of P value and EE of NiHCF / Zn-LDH battery during hot charging and normal charging. Fig.24As shown in the figure, under the two charging modes, the P value and EE gradually decrease with the increase of the number of cycles. After 8 electrochemical Stirling cycles of variable temperature charge and discharge, the P value decayed from 103.35% to 101.54%, but it was still much higher than the highest P value of 91.97% when the battery was charged and discharged at a constant temperature at 5°C; the energy efficiency of the hot charging battery decreased from 102.34% to 101.66%, and the decay rate was less than 0.7%. The energy efficiency of normal charging decreased from 89.68% in the first cycle to 87.52% in the eighth cycle, and the decay rate was 2.41%. The results show that the NiHCF / Zn-LDH battery can save charging energy well and has good cycle performance during the variable temperature charge and discharge process of charging at 50°C and discharging at 5°C.

[0127] Finally, we assembled a soft pack battery and charged it in the high temperature (48°C) outdoors during the day and the low temperature (5°C) in the basement at night. The results are as follows: Fig.25 (a) and (b). Under the same capacity, the charging voltage of the battery at 5°C is 1.726V, and the charging voltage at 48°C is 1.517V, which is 12.11% lower than the charging voltage at 5°C. It further illustrates that temperature has a great influence on the charging voltage of NiHCF / Zn-LDH batteries, and hot charging can save a large amount of charging energy. In summary, the present invention can successfully increase the energy efficiency of the battery to more than 100% by increasing the temperature coefficient of the battery and using waste heat and electrical energy to charge the battery simultaneously in the constructed electrochemical Stirling cycle.

[0128] After testing, except Ni 2+ In addition, Fe 2+ , Mn 2+ , Cu 2+ ,Co 2+ ,Mg 2+ They can all participate in the reaction to generate a stable hydrotalcite-like structure with hydrogen bonds between layers, and effectively improve the P value and EE of the battery.

[0129] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0130] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. An electrochemical energy storage device, characterized in that: The invention comprises a first positive electrode, a first negative electrode and a first electrolyte, wherein the active material of the first positive electrode is NiHCF; the first electrolyte comprises KCF3SO3, Zn(CF3SO3)2 and NiSO4; the first negative electrode is a composite material of zinc surface modified double hydroxide, the composite material comprises a matrix layer and a modified layer, the matrix layer comprises zinc metal and / or zinc alloy, and the structural formula of the modified layer is: Zn 3.52 Ni 1.63 (SO4) 1.33 (OH) 7.64 4.67H2O; The modified layer is composed of Zn(OH)2 and Ni(OH)2, and the interlayer is composed of ZnSO4, -OH and H2O; The preparation of the composite material comprises the following steps: Removing the oxide layer on the surface of the substrate layer, using the substrate layer as a second negative electrode, assembling a battery with a second positive electrode and a second electrolyte, and performing constant current charge and discharge at a current density of 0.01-0.1 mA / g for at least one cycle to obtain the composite material; Wherein, the active material of the second positive electrode is NiHCF, and the second electrolyte includes KCF3SO3, Zn(CF3SO3)2 and NiSO4; The electrochemical energy storage device was charged at 50°C and discharged at 5°C. When the current density was 11.2 mA·g -1 When charging, the thermoelectric efficiency is 4.07%, the P value is 104.13%, and the EE value is 104.11%.

2. The electrochemical energy storage device according to claim 1, characterized in that: In the first electrolyte, the concentration of KCF3SO3 is 0~3M, the concentration of Zn(CF3SO3)2 is 0~4M, and the concentration of NiSO4 is 0~3M.

3. The electrochemical energy storage device according to claim 1, characterized in that: In the second electrolyte, the concentration of KCF3SO3 is 0~3M, the concentration of Zn(CF3SO3)2 is 0~4M, and the concentration of NiSO4 is 0~3M.

Citation Information

Patent Citations

  • Environment heat-oxygen capture efficient thermoelectrochemical system and working method thereof

    CN115347252A

  • Preparation method and application of micron-sized iron-based Prussian blue material

    CN115710003A

  • Layered double hydroxide surface modified zinc battery negative electrode and preparation method thereof

    CN116207212A

  • A method for producion of the layered double hydroxides by irradiation

    KR1020160108688A

  • Secondary Alkaline Electrochemical Cells with Zinc Anode

    US20210043921A1